Rre37 stimulates accumulation of 2-oxoglutarate and glycogen under nitrogen starvation in Synechocystis sp. PCC 6803 - Joseph, Ancy; Aikawa, Shimpei; Sasaki, Kengo; Teramura, Hiroshi; Hasunuma, Tomohisa; Matsuda, Fumio; Osanai, Takashi; Hirai, Masami Yokota; Kondo, Akihiko (FEBS letters, 2014)
•Metabolomic analysis was applied on the Rre37 mutant of Synechocystis.•Role of Rre37 under nitrogen starvation was investigated.•2-Oxoglutarate accumulation was abolished in the Rre37 mutant.•Rre37 regulated glycogen accumulation through glycogen anabolism.•Rre37 regulated accumulation of TCA cycle metabolites. Rre37 (sll1330) in a cyanobacterium Synechocystis sp. PCC 6803 acts as a regulatory protein for sugar catabolic genes during nitrogen starvation. Low glycogen accumulation in Δrre37 was due to low expression of glycogen anabolic genes. In addition to low 2-oxoglutarate accumulation, normal upregulated expression of genes encoding glutamate synthases (gltD and gltB) as well as accumulation of metabolites in glycolysis (fructose-6-phosphate, fructose-1,6-bisphosphate, and glyceraldehyde-3-phosphate) and tricarboxylic acid (TCA) cycle (oxaloacetate, fumarate, succinate, and aconitate) were abolished by rre37 knockout. Rre37 regulates 2-oxoglutarate accumulation, glycogen accumulation through expression of glycogen anabolic genes, and TCA cycle metabolites accumulation.